The relation of pericoronal third molar follicle dimension and bcl-2/ki-67 expression: An immunohistochemical study - Seyed Mohammad Razavi; Daryush Hasheminia; Mojde Mehdizade; Bijan Movahedian; Forouz Keshani (Wolters Kluwer Medknow Publications, 2012)
Background: Most common impacted teeth are the mandibular third molars and decision about extraction of them is usually controversial. The presence of pericoronal pathologic changes is an acceptable reason for removal of impacted teeth. Differences in the proliferation rate and apoptosis of odontogenic epithelial cells may influence on the formation of odontogenic epithelial lesions. Therefore, the aim of the present study is to evaluate the immunohistochemical expression of the bcl-2 apoptosis-inhibiting protein and the cell-cycle-related ki-67 antigen in pericoronal follicle of impacted third molars with ≥2.5 mm and <2.5 mm radiolucency. Materials and Methods: This was a cross-sectional study that 20 follicles with <2.5 mm radiolucency and 20 follicles with ≥2.5 mm radiolucency were selected by a professional radiologist in digital panoramic radiographs and then referred to a surgeon. Formalin fixed paraffin-embedded tissues were immunohistochemical analyzed for immunoreactivity of bcl-2 protein and ki-67 antigen. The data was analyzed using logistic regression, Spearman correlation coefficient and t-test and Mann-Whitney. P<0.05 was considered significant. Results: The findings showed correlation between size of the third molar's follicles and expression of bcl-2 protein (P < 0.001, r = 0.556) but there was no correlation between size of third molar's follicles and staining with ki-67 antigen (P = 0.546, r = 0.098). The follicles with radiolucency ≥2.5 mm showed increased immunoreactivity for bcl-2 protein. Conclusion: The results of study suggest that impacted third molars with radiolucency ≥2.5 mm may be associated with deregulation of cell death, indicated with increased expression of the anti- apoptotic protein bcl-2, while cell proliferation (ki-67) does not seem to play a significant role.